Post-Crisis Exchange Rate Policy in Five Asian Countries : Filling in the "Hollow Middle"? - Hernandez, Leonardo (IMF Working Papers; Working Paper, 2001)
Following the 1997-98 financial turmoil, crisis countries in Asia moved toward either floating or fixed exchange rate systems, reinforcing the bipolar view of exchange rate regimes and the "hollow middle" hypothesis. But some academics have claimed that the crisis countries' policies have been similar in the post- and pre-crisis periods. This paper analyzes the evidence and concludes that, except for Malaysia, which adopted a hard peg and imposed capital controls, the other crisis countries are floating more than before, though less than "real" floaters do. Further, the crisis countries' policies during the post-crisis period can be justified on second-best arguments.